2013
DOI: 10.1111/gfs.12092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two additives on the fermentation, in vitro digestibility and aerobic security of Sorghum–sudangrass hybrid silages

Abstract: Two additives (Silo Guard (SG) and propionic acid (PA)) were tested for their effects on the quality and aerobic security of sorghum–sudangrass hybrid silages (JC‐1 and WC‐2). Two sorghum–sudangrass hybrid varieties were harvested for ensiling without additives (CK) or after the following treatments: SG at 0·5% of fresh forage or PA at 0·5% of fresh forage, with three replicates per treatment. The addition of SG and PA both affected the fermentation quality and chemical composition of the silages by lowering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
2
21
1
2
Order By: Relevance
“…According to Han and colleagues (), 20 g of each silage sample was homogenized with 180 ml of distilled water in a blender for 1 min and then filtered through four layers of cheesecloth and filter paper. The pH of this filtrate was measured by a glass electrode pH meter (PHS‐3C, INESA Scientific Instrument, Shanghai, China) immediately.…”
Section: Methodsmentioning
confidence: 99%
“…According to Han and colleagues (), 20 g of each silage sample was homogenized with 180 ml of distilled water in a blender for 1 min and then filtered through four layers of cheesecloth and filter paper. The pH of this filtrate was measured by a glass electrode pH meter (PHS‐3C, INESA Scientific Instrument, Shanghai, China) immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Lactic acid contents in P and PL silages increased (P<0.001) from the beginning of aerobic stability test to day 9 and then decreased, however, they were still above the initial value (at silo opening) on day 12. This may be due to volatilization and/or metabolism of propionic acid during aerobic exposure, which would allow lactate producers to produce lactic acid under aerobic conditions as suggested by Han et al (2015). The pH in P and PL silages was maintained relatively constant throughout the whole stage of aerobic exposure.…”
Section: Aerobic Stabilitymentioning
confidence: 98%
“…Aerobic deterioration of silage is unfavorable as a consequence of the nutritional losses, and the proliferation of potentially pathogenic or otherwise undesirable microorganisms and mycotoxin synthesis, which can pose health hazards to animals and humans (Richard et al 2009). Propionic acid has been used to inhibit yeasts that assimilate lactic acid when silages are exposed to air and thus, they improve aerobic stability (Han et al 2015). Kung et al (1998Kung et al ( , 2000 found that weak organic acid with strong antifungal prop-erties, such as propionic acid, applied at 0.2-0.3% of fresh forage weight, could improve the stability of corn silage, but this additive showed minor efficiency of fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on ensiling technology for sorghum-sudangrass hybrids has focused on the regulation of silage materials (AKDENIZ et al, 2012;BI et al, 2018;GUL et al, 2008;JIANG et al, 2005) and additives (DOLEZAL, 2009;HAN et al, 2015;ZHANG et al, 2010). Chopped straw is a most effective absorbent, consequently, mixing straw with grass is an accepted technique for reducing effluent loss, increasing dry matter and improving fermentation quality of mixed silage (GALLEGOS et al, 2018).…”
Section: Introductionmentioning
confidence: 99%